2002
DOI: 10.1007/s00109-002-0346-2
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 gene modified immature dendritic cells exhibit enhanced tolerogenicity but induce allograft fibrosis in vivo

Abstract: Administration of donor-derived immature dendritic cells (DC) can prolong the survival of MHC-mismatched cardiac allografts. Genetic modification of DC by immunosuppressive molecules can enhance their potential tolerogenicity. In this study bone marrow derived immature DC were genetically modified by transforming growth factor (TGF) beta1 by recombinant Ad. TGF-beta(1) gene modified immature DC (TGF-beta-DC) displayed a characteristic phenotype of immature DC, decreased ability to secrete interleukin 12, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…Culture supernatants of TGF-b1-DCs or LacZ-DCs were harvested 48 h after transfection of Ad-TGF-b1 or Ad-LacZ, 13 respectively; culture supernatants of day-6 DCs were used as a control. The level of TGF-b1 was detected by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Culture supernatants of TGF-b1-DCs or LacZ-DCs were harvested 48 h after transfection of Ad-TGF-b1 or Ad-LacZ, 13 respectively; culture supernatants of day-6 DCs were used as a control. The level of TGF-b1 was detected by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…To provide a comparison between the effects of direct TNF-␣ blockade by secreted sTNFRI and those of DC-sTNFRI in vivo, 2 ϫ 10 6 sTNFRI genemodified L929 cells (L929-sTNFRI, H-2 d ), which secreted comparable levels of sTNFRI to DC-sTNFRI in vitro, were infused into separate recipients. On day 0, fully allogeneic cervical vascularized heart transplantation was performed from C57BL/6 or C3H (as third-party) donors to size-matched BALB/c recipients as described previously (12). Graft survival was assessed by daily palpation of grafted hearts, with rejection defined as total cessation of cardiac contraction.…”
Section: Heterotopic Heart Transplantation and Skin Transplantationmentioning
confidence: 99%
“…Our previous studies showed that the efficacy of Ad-mediated transfection of BM-derived DC was Ͼ95% (12,30). First, the levels of sTNFRI in supernatants of gene-modified DC were determined.…”
Section: Resistance Of Dc-stnfri To Maturation Inductionmentioning
confidence: 99%
“…Though TGF-b and IL-10 are commonly accepted to be important for the induction of tolerance [28][29][30][31], both are not involved in the inhibitory functions of DCreg. It is well known that NO, PGE2 and IDO can all inhibit T-cell proliferation by acting upon multiple signaling pathways [32].…”
Section: Discussionmentioning
confidence: 99%